Revitalizing Heritage Districts at Tasikmalaya Station: Integrating Respectful Facade Articulation and Architectural Business Strategies - Fajar Rezandi; Cut Sannas Saskia; Maria Immaculata Ririk Winandari; Teungku Nelly Fatmawati; Nisrina Rahma Ningsih (Universitas Negeri Yogyakarta, 2026)
The development of heritage transit districts ideally integrates respectful facade articulation design, adaptive architectural practices that respect historical values, and sustainability-oriented business strategies. This approach enables the preservation of cultural identity while generating new economic value through adaptive reuse and strategic place branding. Tasikmalaya Station is a heritage building that functions as a key transportation hub in East Priangan. However, the surrounding district faces challenges, including the degradation of heritage functions, suboptimal connectivity, and a lack of cohesive business models integrated with cultural potential. Revitalizing heritage areas like Tasikmalaya Station often faces a dilemma between preserving historic facades and meeting the demands for modern design and functionality. When innovative design is not aligned with business strategy, interventions risk becoming unsustainable and losing socio-economic relevance. This study explores how respectful facade articulation design, adaptive architectural reuse, and business strategies can be integrated to realize a sustainable and strategically valuable heritage-based TOD area. The study employs a literature review approach, synthesizing open-access scholarly journals on adaptive facades, reuse strategies, and architecture-driven business models. The selected literature is contextually aligned with the Tasikmalaya Station masterplan. Three interrelated dimensions respectful facade articulations, adaptive reuse, and business strategies mutually reinforce each other in shaping productive and relevant heritage districts. Respectful facade enhances visual identity and building performance; adaptive architecture maintains cultural continuity and contemporary function; while business strategies support sustainability through community branding and alternative funding models.